2022
DOI: 10.1039/d2dt00856d
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-oxo clusters for photocatalytic aerobic oxygenation of sulfides to sulfoxides

Abstract: Two cerium-oxo clusters (COCs) 1 and 2 are constructed by self-assembly of cerium ions and carboxylate ligands. Both clusters feature spherical structures resembling the key moiety of fluorite phase CeO2,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…As shown in Scheme 2, under white LED light irradiation, LCU-20 could be excited and electron transfer occurred. Simultaneously, MPS lost electrons to form the corresponding radical cation (MPS radical cation) through photogenerated holes in the HOMO orbitals of LCU-20 , 48 and O 2 was reduced to the reactive oxygen species O 2 ˙ − by photogenerated electrons in the LUMO orbitals. 49 Subsequently, O 2 ˙ − combined with the radical cation to further form the methyl phenyl persulfoxide intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 2, under white LED light irradiation, LCU-20 could be excited and electron transfer occurred. Simultaneously, MPS lost electrons to form the corresponding radical cation (MPS radical cation) through photogenerated holes in the HOMO orbitals of LCU-20 , 48 and O 2 was reduced to the reactive oxygen species O 2 ˙ − by photogenerated electrons in the LUMO orbitals. 49 Subsequently, O 2 ˙ − combined with the radical cation to further form the methyl phenyl persulfoxide intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…State-of-the-art preparation of monodisperse ceria nanoparticles are often executed in organic solvent with capping groups to control and maintain particle size. , Additionally, molecular Ce IV clusters have been crystallized from all types of media and with different capping groups, highlighting the tendency of Ce IV to undergo hydrolysis/condensation reactions. Of these, a subfamily of spherical clusters consisting of 16, 19, 24, 38, 40, and 100 Ce-polyhedra have been crystallized from organic media with carboxylate and solvent capping ligands, and Ce 38 has also been isolated from HCl solution . In this family, the arrangement of the Ce-polyhedra resembles that of CeO 2 , and their sizes (specifically Ce 38 , Ce 40 , and Ce 100 ) are similar to the observed primary particle size of CeO 2 that precipitates from aqueous cerium ammonium nitrate (CAN) .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most notable industrial applications of ceria is its use in three-way catalysts (TWCs); ceria can serve several purposes for TWCs, including acting as an oxygen storage component due to its reduction potential. , In fact, the accessibility of the +3 and +4 oxidation states prompts many efforts that seek to harness the redox chemistry of cerium toward uses in optics, solid-oxide fuels, and oxygen storage. Largely motivated to (1) better understand the catalytic behavior of CeO 2 and (2) develop novel Ce-based catalysts that can be fine-tuned for specific applications, the chemistry community has become interested in cerium-oxo clusters. These species can be regarded as molecular scale nanoparticles of CeO 2 , and their properties seem to depend on the nuclearity and composition of the Ce cluster . As a testament, Christou et al recently demonstrated the ability of Ce-oxo clusters to scavenge reactive oxygen species, and the activity of these clusters was dependent on the number of Ce III atoms present in the cluster .…”
Section: Introductionmentioning
confidence: 99%